2013
DOI: 10.1002/clc.22200
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics in Cardiovascular Disease: The Challenge of Moving From Promise to Realization

Abstract: Pharmacogenetics in cardiovascular medicine brings the potential for personalized therapeutic strategies that improve efficacy and reduce harm. Studies evaluating the impact of genetic variation on pharmacologic effects have been undertaken for most major cardiovascular drugs, including antithrombotic agents, β-adrenergic receptor blockers, statins, and angiotensin-converting enzyme inhibitors. Across these drug classes, many polymorphisms associated with pharmacodynamic, pharmacokinetic, or surrogate outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Several studies have demonstrated a significant link between angiotensin converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism and cardiovascular outcomes. However, the impact of this genetic polymorphism on ACE inhibitor response is not well understood [40,41].…”
Section: Application Of Methods To Volunteer Dbs Samplesmentioning
confidence: 99%
“…Several studies have demonstrated a significant link between angiotensin converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism and cardiovascular outcomes. However, the impact of this genetic polymorphism on ACE inhibitor response is not well understood [40,41].…”
Section: Application Of Methods To Volunteer Dbs Samplesmentioning
confidence: 99%
“…The individual response to various drugs used for treatment of CHF is highly variable and this variability cannot solely be explained by differences in clinical characteristics of patients [ 19 – 21 ]. Accordingly, genetic variations have been suggested to have a considerable effect on drug response and in patients treated with ACEIs the ACE I/D polymorphism has been a focus of attention [ 9 , 22 , 23 ]. Indeed, high circulating ACE activity has been associated with this polymorphism and with worse cardiovascular outcomes in CHF patients [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, high circulating ACE activity has been associated with this polymorphism and with worse cardiovascular outcomes in CHF patients [ 24 ]. Nonetheless, the utility of the ACE I/D polymorphism for pharmacogenetic risk stratification in CHF patients remains contentious, which may be explained, in part, by an anticipated small impact of this polymorphism on ACEI efficacy, and by the fact that published results have been limited by small study populations [ 22 , 25 , 26 ]. A few other genetic polymorphisms have separately been associated with the efficacy and safety of ACEIs, including some of those represented in the current study (rs4343, rs495828 and rs817646) [ 10 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the successful use of pharmacogenomics in the clinic has been limited (Urban and Goldstein, 2014) and recent reviews of the use of pharmacogenomics in randomized clinical trials in cardiovascular disease (Joseph et al, 2014), type-2 diabetes (Maruthur et al, 2014), and depression (Perlis, 2014) have failed to show clear value.…”
Section: Introductionmentioning
confidence: 99%